An Adaptive Management Model of Islamic Education toward Social and Cultural Transformation - Mubaidilla, Trias Fatih; Mubaidilla, Irfa’i Alfian (Journal of Educational Management and Strategy, 2025)
This study aims to formulate an adaptive management model for Islamic education that responds effectively to the dynamics of contemporary socio-cultural change. Using a qualitative approach grounded in a comprehensive literature review, the analysis explores the principles of Islamic educational management, organizational adaptation theory, and relevant institutional management practices. The findings present a cyclical adaptive model that emphasizes four interrelated stages: scanning the environment, aligning values, implementing changes, and conducting evaluation. The first stage involves mapping institutional conditions, community characteristics, and educational needs. The second focuses on adjusting management policies to remain consistent with Islamic principles and local contexts. The third concerns the practical and measurable implementation of adaptive strategies, while the final stage involves continuous assessment to ensure ongoing improvement. The proposed model highlights the importance of stakeholder participation, contextualized curricula, educator capacity development, and collaborative evaluation mechanisms. The study suggests that effective adaptive management in Islamic education requires the integration of flexibility with moral and spiritual values to maintain relevance in a rapidly changing society. The implication is that educational leaders must adopt responsive and sustainable management approaches to preserve the quality and integrity of learning. This research contributes a conceptual framework that can guide Islamic educational institutions in navigating transformation while upholding their ethical and spiritual foundations. Future research is encouraged to empirically examine the model’s applicability and effectiveness in diverse institutional contexts.